Le dernier homme : version nouvelle - Latzko, Andreas; Masereel, Frans; Zweig, Stefan; Arcos, René; Roget, David (Genève : Editions du Sablier, 1920)
Bibliotheek Jan Baghus
Genummerd exemplaar, nr 224.
Frans
Monografie
Keywords: romans